Pengembangan Media Pembelajaran Sejarah Indonesia Berbasis Infografis Materi Kekuasaan Kongsi Dagang VOC di SMA Negeri 10 Medan - Mastrida Nainggolan; Mhd. Ihsan Syhaf Nasution (Journal on Education, 2023)
The use of learning media is increasingly being used day by day. History is one example of a subject that feels quite high benefits from the use of learning media. This research aims to develop infographic media in history learning at the high school level. To determine the quality of infographic media as a learning medium in terms of feasibility validation aspects, and to determine the effectiveness of infographic media in learning based on student learning outcomes. This research was carried out at SMA Negeri 10 Medan, with the research sample being class X IPS 1. This research used the R&D method. The data collection technique is in the form of a questionnaire or questionnaire, while the data analysis technique uses percentage calculations. The results of this research indicate that the media developed meets the requirements and is suitable for use as learning media. The validation results of material experts and media experts respectively obtained a score percentage of 98% and 96%. Meanwhile, the results of small group trials showed a score percentage of 84%. Then, the results of large group use trials and effectiveness tests respectively showed a score percentage of 84% and 93%. With these results, it can be concluded that this infographic media is very valid and therefore suitable and effective for use in learning.